G156 Sickle Cell Disease in Malawian Children is Associated with Restrictive Spirometry: A Cross Sectional Survey. (4th June 2013) - Cook, JWA; Jefferis, O; Matchere, P; Mbale, E; Rylance, J
Abstract : Introduction: Children with sickle cell disease (SCD) more commonly exhibit clinical features of asthma than the general population. The pathogenesis of this observation remains unclear. However these individuals are at increased risk of acute chest syndrome 1, and recurrent episodes of this complication strongly predict the development of sickle chronic lung disease 2 . It is postulated that lung function in these children is typically "obstructive" in early life and becomes "restrictive" in adulthood. Aim: To assess lung function and symptoms of asthma in Malawian children with SCD. Methods: Children with electrophoretically confirmed SCD attending our clinic were consecutively recruited to undergo spirometry and questionnaire screening of asthma symptoms. Forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC) and FEV1/FVC ratio were compared with local and international reference ranges3, 4. Asthma symptoms were recorded using the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. Results: Twenty-four children aged 7 to 16 were recruited (median age 11.5 years, IQR 8 to 13.5). Mean spirometric indices represented as z-scores derived from international reference ranges3 were low (Fig. 1 ): FEV1 –1.64 (95% CI –2.04 to –1.23), FVC –1.49 (95% CI –1.90 to –1.09), FEV1/FVC –0.39 (95% CI –0.76 to –0.03). No individual exhibited evidence of an obstructive defect. Comparison with local reference ranges 4, represented as percentage of predicted value, revealed similar impairments (Fig. 2 ): FEV1 86.9 (95% CI 81.1 to 92.7), FVC 89.0 (95% CI 83.5 to 94.4), FEV1 /FVC ratio 97.7 (95% CI 95.4 to 99.9). FEV1 /FVC ratios are also given as absolute values (Fig. 2 ). The prevalence of wheeze among the participants was lower than that recorded in a proximate African population 5 (Tab. 1). Conclusion: We have demonstrated lung function abnormalities suggestive of restrictive lung disease, and wheeze prevalence comparable to that of a cohort without SCD. The progression of the pulmonary complications associated with SCD may differ significantly between populations suggesting an important role of environmental influences. References: Boyd JH, DeBaun MR, Morgan WJ, Mao J, Strunk RC. Lower airway obstruction is associated with increased morbidity in children with sickle cell disease. Pediatr Pulmonol. 2009; 44(3):290–296. Knight-Madden JM, Forrester TS, Lewis NA, Greenough A. The impact of recurrent acute chest syndrome on the lung function of young adults with sickle cell disease. Lung. 2010; 188(6):499–504. Wang X, Dockery DW, Wypij D, Fay ME, Ferris BG. Pulmonary function between 6 and 18 years of age. Pediatr Pulmonol. 1993; 15(2):75–88. Zverev Y, Gondwe M. Ventilatory capacity indices in Malawian children. East Afr Med J. 2001; 78(1):14–18. Mavale-Manuel S, Joaquim O, Nunes E et al Prevalence of asthma-like symptoms by ISAAC video questionnaire in Mozambican schoolchildren. Monaldi Arch Chest Dis. 2006; 65(4):189–195.